ENHANCING MUSCULAR STRENGTH AND ENDURANCE AMONG STUDENTS WITH PHYSICAL DISABILITIES THROUGH A SEATED PHYSICAL ACTIVITY MODULE: A QUASI-EXPERIMENTAL STUDY - Zainudin, Aisyah; Irin, Eshelvana Elve; Othman, Syuhadah; Nazarudin, Mohamad Nizam (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Physical inactivity remains a critical challenge among students with physical disabilities, often resulting in reduced muscular strength, endurance, and functional independence. This study aimed to evaluate the effectiveness of a structured Seated Physical Activity (SPA) module in improving muscular fitness among students with physical disabilities within an inclusive education context. A quasi-experimental single-group pretest–posttest design was conducted with 22 students aged 13–17 years diagnosed with mild to moderate physical disabilities. Over eight weeks, participants completed two weekly SPA sessions comprising warm-up, seated resistance exercises, and cool-down phases. Three validated instruments, the Hand Grip Strength Test, 5-Repetition Sit-to-Stand Test, and 30-Second Chair Stand Test, were used to assess upper- and lower-body performance. Data were analysed using paired-sample t-tests and Cohen’s d for effect size estimation. Significant improvements were observed in hand grip strength (t = 5.48, p < .001, d = 1.17), sit-to-stand endurance (t = 6.12, p < .001, d = 1.30), and chair stand repetitions (t = 5.77, p < .001, d = 1.23). These findings indicate large effect sizes and confirm the SPA module’s effectiveness in enhancing both upper- and lower-limb performance. The SPA module demonstrates high validity (CVI = 0.92) and feasibility for school implementation. Its evidence-based design supports Motor Learning Theory, Physical Adaptation Theory, and Self-Determination Theory, enabling inclusive and low-cost physical education delivery for students with disabilities. This study offers one of the first empirical validations of a seated physical activity intervention in Malaysian special education, presenting a replicable model to promote inclusive, safe, and effective exercise participation in schools.